(untitled) (Contemporary Journal of Social Science Review, 2025)
Conversion disorder is becoming a more prevalent mental health issue among young individuals. To comprehend early traumas, coping mechanisms, self-defense mechanisms, and schemas, such instances require an in-depth study. An 18-year-old girl presented with seizures, loss of sensation, throat constriction, and extreme anger issues. Formal assessment using the Symptom Checklist (SCL-R) led to a diagnosis of Functional Neurological Symptom Disorder (Conversion Disorder F44) based on DSM-5-TR criteria. Cognitive Behavioral Therapy (CBT) was implemented alongside parental counseling to address underlying schemas, trauma, and coping mechanisms. A total of 14 sessions were conducted, resulting in a 70% improvement. The case highlights the importance of strong parental support and a therapeutic alliance in effective treatment, reducing reliance on medication and risk of relapses.